Training on the Role of Artificial Intelligence in Network Security for Vocational High School Students at SMK St. Louis Surabaya - Kharisma Monika Dian Pertiwi; Emmanuel Satria Anugrah Dewangga; Pandu Rafa Panatagama; Akbar Muhammad Sadat; Alisina Mutirazin Ghazalah Muslimin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
A training on the role of artificial intelligence (AI) in network security was conducted for 12th‑grade students of the Computer and Network Engineering program at SMK St. Louis Surabaya. The material combined an introduction to cyber threats, AI concepts, the role of AI in network security, a demonstration and hands‑on practice of anomaly detection using an LSTM Autoencoder model on a network log dataset via Google Colab. Participant satisfaction evaluation showed a positive response with an average score of 4.265 (scale 1–5). However, the training duration still requires adjustment. Recommendations include adjusting the training duration, implementing quantitative competency assessments, and conducting field tests to measure the model’s performance on real network traffic.